Positive electrode material, positive electrode including the positive electrode material, and lithium battery including the positive electrode

By using carbon materials with secondary particles in the positive electrode material of lithium-ion batteries, the problem of microcracks of the positive electrode material during charging and discharging is solved, the battery capacity is increased and the resistance is reduced, and the battery energy density and life is improved. .

CN113206254BActive Publication Date: 2025-02-14SAMSUNG SDI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110479918.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2014-08-13
Filing Date
2015-08-13
Publication Date
2025-02-14
Estimated Expiration
2035-08-13

AI Technical Summary

Technical Problem

The positive electrode materials of existing lithium-ion batteries are prone to microcracks during charging and discharging, resulting in a decrease in battery capacity and an increase in resistance, affecting the energy density and life of the battery.

Method used

Using a positive electrode material including a positive electrode active material and a carbon material of secondary particles, the carbon material of secondary particles consists of a plurality of primary particles, and the carbon material of secondary particles has an average chain of 50 primary particles that are equal to or less than one another. length.

Benefits of technology

By improving the dispersion and electronic conductivity of the positive electrode material, the battery capacity is increased and the resistance is reduced, and the energy density and life of the lithium-ion battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113206254B_ABST
    Figure CN113206254B_ABST
Patent Text Reader

Abstract

The positive electrode material includes: a positive electrode active material; a carbon material of secondary particles, including a plurality of primary particles, wherein the carbon material of the secondary particles has an average chain length equal to or less than 50 primary particles bonded to each other. The positive electrode includes a positive electrode material and a current collector. The lithium battery includes a positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of a patent application filed on August 13, 2015, with application number 201510497855.4 and entitled “Positive electrode material, positive electrode including positive electrode material and lithium battery including positive electrode”. Technical Field

[0002] One or more example embodiments relate to a positive electrode material, a positive electrode including the positive electrode material, and a lithium battery including the positive electrode. Background Art

[0003] The demand for secondary batteries used in mobile electronic devices for information and communication (including personal digital assistants, cellular phones and laptops) and electric bicycles or electric vehicles is growing rapidly. Lithium batteries (e.g., lithium ion batteries (LIBs)) have high energy density and are easy to design, so in addition to being used in portable information technology (IT) devices, they are also used as power sources for electric vehicles or power storage. Lithium ion batteries should have high energy density and / or long life characteristics.

[0004] Research on positive electrode materials has been conducted to manufacture lithium-ion batteries with suitable characteristics. However, for example, due to reduced contact between the positive electrode active material and the current collector, oxidation of the conductive material, stress caused by repeated charging / discharging of the battery and / or a rolling process used during the positive electrode manufacturing process, micro cracks are generated in the positive electrode active material, and thus, the capacity of the battery is reduced and the resistance of the battery is increased. Summary of the invention

[0005] One or more aspects of example embodiments include a positive electrode material having high energy density and / or long life characteristics by increasing battery capacity and reducing resistance.

[0006] One or more aspects of example embodiments include a positive electrode including a positive electrode material.

[0007] One or more aspects of example embodiments include a lithium battery having a positive electrode.

[0008] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments.

[0009] According to one or more embodiments, a positive electrode material includes: a positive electrode active substance; a carbon material of secondary particles, including a plurality of primary particles (for example, composed of a plurality of primary particles), and the carbon material of the secondary particles has an average chain length equal to or less than 50 primary particles combined (or connected) with each other.

[0010] According to one or more embodiments, a positive electrode includes a positive electrode material and a current collector.

[0011] According to one or more embodiments, a lithium battery includes: a positive electrode including a positive electrode material; a negative electrode including a negative electrode active material; and an electrolyte located between the positive electrode and the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] These and / or other aspects will become apparent and more readily understood from the following description of example embodiments taken in conjunction with the accompanying drawings, in which:

[0013] Figure 1A is a schematic diagram of a positive electrode material according to an embodiment;

[0014] Figure 1B is a schematic diagram of a positive electrode material prepared according to Comparative Example 1;

[0015] Figure 2A and Figure 2B The images are respectively images of the positive electrode materials on the surface of the positive electrode prepared according to Example 1 and Comparative Example 1, and the images are acquired using a transmission electron microscope (HR-TEM) with a resolution of tens of nanometers (nm);

[0016] Figure 2C and Figure 2D The images are respectively images of the positive electrode materials on the surface of the positive electrodes prepared according to Example 1 and Comparative Example 1, and the images are acquired using a transmission electron microscope (HR-TEM) with a resolution of several hundred nanometers (nm);

[0017] Figure 3A and 3B The images are respectively images of the positive electrode materials on the surface of the positive electrodes prepared according to Example 1 and Comparative Example 1, and the images are acquired using a scanning electron microscope (SEM) with a resolution of several hundred nm;

[0018] Figure 4 is a graph showing a change in viscosity of a positive electrode material on the surface of each positive electrode prepared according to Example 1 and Comparative Example 1 with respect to a shear rate;

[0019] Figure 5 is an exploded perspective view of a lithium battery according to an embodiment;

[0020] Figure 6 is a perspective view schematically showing a battery pack according to an embodiment;

[0021] Figure 7 is a graph showing resistance of each lithium battery prepared according to Example 3 and Comparative Example 3 at SOC 20%, SOC 50%, and SOC 90%, respectively;

[0022] Figure 8is a graph showing the life characteristics of the lithium batteries prepared according to Example 3 and Comparative Example 3 after being kept for 60 days;

[0023] Fig. 9 is a graph showing the service life characteristics of the lithium batteries prepared according to Example 4 and Comparative Example 4 measured using a reference performance test on 18650 batteries. DETAILED DESCRIPTION

[0024] Reference will now be made in more detail to the example embodiments of the positive electrode material, the positive electrode including the positive electrode material and the lithium battery including the positive electrode, examples of the example embodiments are shown in the accompanying drawings, wherein the same reference numerals always indicate the same element. In this regard, the current example embodiments may have different forms and should not be construed as being limited to the descriptions set forth herein. Therefore, the example embodiments are described below with reference to the accompanying drawings only to explain the various aspects of this description. As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items. When a statement such as "at least one (individual / person) of ... is behind a series of elements, it modifies the elements of the entire series, rather than modifying a single element in the series. In addition, in the context of the present application, when a first element is referred to as "on" a second element, the first element may be directly on the second element, or may be indirectly on the second element and one or more intermediate elements may be placed between the first element and the second element. As used herein, the terms "substantially", "approximately" and similar terms are used as approximate terms rather than terms of degree, and are intended to illustrate the inherent deviations of measured or calculated values ​​that will be recognized by those of ordinary skill in the art. In addition, any numerical range described here is intended to include all sub-ranges of the same numerical precision included in the description range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between the minimum value 1.0 described and the maximum value 10.0 described (and including the minimum value 1.0 and the maximum value 10.0), that is, having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical upper limit described here is intended to include all smaller numerical upper limits included here, and any minimum numerical lower limit described in this specification is intended to include all larger numerical lower limits included here. Therefore, the applicant reserves the right to modify this specification, including the claims, to explicitly describe any sub-range included in the scope explicitly described here. All such ranges are intended to be inherently described in this specification so that modifications to explicitly describe any such sub-ranges will meet the relevant requirements.

[0025] Figure 1A is a schematic diagram of a positive electrode material according to an embodiment. Figure 1B is a schematic diagram of the positive electrode material prepared according to Comparative Example 1.

[0026] Reference Figure 1A According to an embodiment, the positive electrode material includes: a positive electrode active substance 1; a carbon material 2 of secondary particles, including a plurality of primary particles or consisting of a plurality of primary particles, wherein the carbon material 2 of the secondary particles has an average chain length equal to or less than 50 primary particles combined (or connected) with each other. For example, the carbon material 2 of the secondary particles may have an average chain length equal to or less than 30 primary particles combined (or connected) with each other. For example, the carbon material 2 of the secondary particles may have an average chain length equal to or less than 20 primary particles combined (or connected) with each other. For example, the carbon material 2 of the secondary particles may have an average chain length equal to or less than 15 primary particles combined (or connected) with each other. For example, the carbon material 2 of the secondary particles may have an average chain length ranging from about 2 to about 15 primary particles combined (or connected) with each other. It can be achieved by FIG. 2A to FIG. 2D , Figure 3A and Figure 3B The average chain length of the secondary particles of the carbon material 2 was measured using transmission electron microscopy (TEM) images and scanning electron microscopy (SEM) images.

[0027] The secondary particles of carbon material 2 may generally have a length shorter than, for example, Figure 1B The average chain length of the carbon material included in the other positive electrode materials shown in . For example, Figure 1B As can be seen in the figure, the positive electrode material prepared according to Comparative Example 1 includes: a positive electrode active material 3; a carbon material 4 of secondary particles, the average chain length of which is longer than 50 primary particles bound (or connected) to each other. In this regard, relative to the positive electrode material including a carbon material of secondary particles having an average chain length longer than 50 primary particles bound (or connected) to each other, the dispersion of the positive electrode active material 1 and the carbon material 2 included in the positive electrode material can be increased, and the distances of each section of the electron path can be reduced, so the electronic conductivity (conductivity) of the positive electrode material can be increased. In addition, the energy density and / or life characteristics of the positive electrode material can be improved.

[0028] The average particle size of the primary particles may be in the range of about 5 nm to about 30 nm. For example, the average particle size of the primary particles may be in the range of about 10 nm to about 28 nm. For example, the average particle size of the primary particles may be in the range of about 18 nm to about 28 nm. FIG. 2A to FIG. 2D , Figure 3A and Figure 3B The average particle size of the primary particles was measured using transmission electron microscope (TEM) images and scanning electron microscope (SEM) images.

[0029] The specific surface area of ​​the carbon material 2 may be about 100 m 2 / g to about 300m2 For example, the specific surface area of ​​the carbon material 2 may be in the range of about 100 m 2 / g to about 200m 2 For example, the specific surface area of ​​the carbon material 2 may be about 120 m 2 / g to about 200m 2 The specific surface area of ​​the carbon material 2 can be measured by Brunauer-Emmett-Teller (BET) analysis.

[0030] When the primary particles have an average particle size within the above range, the dispersion of the positive electrode active material 1 and the carbon material 2 included in the positive electrode material can be further increased, the specific surface area of ​​the primary particles can be increased, and therefore, the electronic conductivity (conductivity) of the positive electrode material including the primary particles can be further increased. In addition, the energy density and / or life characteristics of the positive electrode material can be further improved.

[0031] The oil absorption (OAN) of the carbon material may be in the range of about 100 ml / 100 g to about 200 ml / 100 g. For example, the oil absorption of the carbon material 2 may be in the range of about 100 ml / 100 g to about 180 ml / 100 g. For example, the oil absorption of the carbon material 2 may be in the range of about 120 ml / 100 g to about 180 ml / 100 g. The oil absorption (OAN) of the carbon material may be obtained by using the ASTM D2414 test method. When a positive electrode material including the carbon material 2 is used, the dispersion of the positive electrode material may be increased during the positive electrode material mixing process, which may cause a reduction in the amount of the organic solvent used thereby, and therefore, the cost of manufacturing a battery including the positive electrode material may be reduced. In addition, due to the reduction in the amount of the organic solvent, the amount of the solid powder of the positive electrode material may be increased, and therefore, a positive electrode material having a stable or suitable viscosity may be manufactured.

[0032] Based on the total weight of the positive electrode material, the amount of carbon material 2 may be in the range of about 1wt% to about 15wt%. For example, based on the total weight of the positive electrode material, the amount of carbon material 2 may be in the range of about 1wt% to about 13wt%. For example, based on the total weight of the positive electrode material, the amount of carbon material 2 may be in the range of about 1wt% to about 10wt%. When the amount of carbon material 2 in the positive electrode material is within the above range, the electronic conductivity (conductivity) and the tap density (packing density) of the positive electrode material may be improved.

[0033] The carbon material 2 may include at least one selected from carbon black (eg, acetylene black and / or Denka Black) and aerogel.

[0034] The positive electrode material may further include at least one additive selected from natural graphite, artificial graphite, carbon black (eg, acetylene black and / or Ketjen black), carbon fiber, metal powder, and metal fiber.

[0035] Based on the total weight of the positive electrode material, the amount of the additive may be in the range of about 0.1wt% to about 15wt%. For example, based on the total weight of the positive electrode material, the amount of the additive may be in the range of about 0.1wt% to about 10wt%. In some embodiments, the amount of the additive may be in the range of about 0.1wt% to about 5wt%. In other embodiments, the amount of the additive is in the range of about 0.1wt% to about 3wt%. When the amount of the additive included in the positive electrode material is within the above range, the battery including the positive electrode material may have an increased capacity and a reduced resistance, and therefore, the lithium battery provided using the positive electrode material may have improved high energy density and / or long life characteristics.

[0036] The positive electrode material may further include a binder. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, or a combination thereof, but the binder is not limited thereto.

[0037] Based on the total weight of the positive electrode material, the amount of the binder may be in the range of about 0.1wt% to about 15wt%. For example, the amount of the binder may be in the range of about 0.1wt% to about 10wt%. In some embodiments, the amount of the binder may be in the range of about 0.1wt% to about 5wt%. In other embodiments, the amount of the binder may be in the range of about 0.1wt% to about 3wt%. When the amount of the binder is within these ranges, the bonding strength between the positive electrode material and the positive current collector may be further enhanced.

[0038] The positive electrode active material 1 can be a compound capable of reversibly intercalating / extracting lithium ions. Examples of the positive electrode active material 1 can include at least one selected from lithium nickelate, lithium cobaltate, lithium cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium manganate, lithium nickelate doped with at least one selected from chromium, zirconium, and titanium, lithium cobaltate doped with at least one selected from chromium, zirconium, and titanium, lithium cobalt aluminum oxide doped with at least one selected from chromium, zirconium, and titanium, lithium nickel cobalt manganese oxide doped with at least one selected from chromium, zirconium, and titanium, lithium manganate doped with at least one selected from chromium, zirconium, and titanium, and at least one selected from olivine-based oxides. For example, the positive electrode active material 1 can include LiMn2O4, LiNi2O4, LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiFePO4, LiNi x Co y O2 (where 0 < x ≤ 0.15 and 0 < y ≤ 0.85), Li a Ni b Co c Mn d G e O2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5 and 0.001 ≤ e ≤ 0.1), Li (3-f) J2(PO4)3 (where 0 ≤ f ≤ 2) or Li (3-f) Fe2(PO4)3 (where 0 ≤ f ≤ 2). In the above formulas, G is Al, Cr, Zr, Ti, or a combination thereof, and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof. However, the positive electrode active material is not limited thereto, and any suitable material available in the art can be used as the positive electrode active material.

[0039] According to another embodiment, the positive electrode includes a positive electrode material and a current collector (for example, the positive electrode material can be located on the current collector). Examples of the current collector can include aluminum, stainless steel, nickel, titanium, platinum, or a combination thereof.

[0040] Based on the total weight of the positive electrode, the amount of the solid of the positive electrode material can be in the range of about 65 wt% or more. For example, based on the total weight of the positive electrode, the amount of the solid of the positive electrode material can be in the range of about 66 wt% or more. Based on the total weight of the positive electrode, the amount of the solid of the positive electrode material can be in the range of about 67 wt% or more.

[0041] The bonding strength between the positive electrode material and the current collector may be in the range of 1.5 gf / mm (gram-force / mm) or greater. For example, the bonding strength between the positive electrode material and the current collector may be in the range of 1.6 gf / mm (gram-force / mm) or greater. For example, the bonding strength between the positive electrode material and the current collector may be in the range of 1.7 gf / mm (gram-force / mm) or greater.

[0042] The specific resistance of the positive electrode may be in the range of about 12 milliohms (mΩ) or less. For example, the specific resistance of the positive electrode may be in the range of about 11 milliohms (mΩ) or less. For example, the specific resistance of the positive electrode may be in the range of about 10 milliohms (mΩ) or less.

[0043] According to another embodiment, a lithium battery includes: a positive electrode including the positive electrode material described above; a negative electrode including a negative electrode active material; and an electrolyte located between the positive electrode and the negative electrode.

[0044] The positive electrode material may be, for example, a paste-type (paste type), a slurry-type (slurry type), or a dispersed solution positive electrode material. According to an embodiment of the present disclosure, for example, the positive electrode material may be prepared as follows.

[0045] The positive electrode material and the solvent are mixed to prepare a positive electrode active material slurry, and the slurry is coated (e.g., directly coated) on an aluminum current collector to prepare a positive electrode. In some embodiments, the positive electrode active material slurry can be cast on a separate support, and the positive electrode active material film separated from the support can be stacked on the aluminum current collector to prepare a positive electrode. The solvent can be an organic solvent, for example, N-methylpyrrolidone (NMP) or acetone.

[0046] Next, the negative electrode may be prepared by the same or substantially the same method as the positive electrode, except that the negative electrode active material is used instead of the positive electrode active material.

[0047] For example, the negative electrode can be prepared as follows.

[0048] A negative electrode active material, a conductive material (conductive material), and an optional binder and a solvent are mixed to prepare a negative electrode active material slurry, and the slurry can be directly coated on a copper current collector to prepare a negative electrode. In some embodiments, the negative electrode active material slurry can be cast on a separate support, and the negative electrode active material film separated from the support can be stacked on the copper current collector to prepare the negative electrode.

[0049] The negative electrode active material may include at least one selected from a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, or a metal material alloyable with lithium.

[0050] Examples of materials capable of reversibly intercalating and deintercalating lithium ions can be carbon-based materials, which can be any suitable carbon-based negative electrode active material commonly used in lithium batteries. Examples of carbon-based materials can be crystalline carbon, amorphous carbon, or mixtures thereof.

[0051] Examples of crystalline carbon include graphite, such as amorphous, plate-like, flaky, spherical (globular) or fibrous natural graphite or artificial graphite. Examples of amorphous carbon include soft carbon (carbon that has been heat-treated at a relatively low temperature), hard carbon, mesophase pitch carbide, and calcined coke.

[0052] Examples of negative electrode active materials can include at least one selected from vanadium oxide, lithium vanadium oxide, Si, SiO x (0 < x < 2), Si-Y alloy (Y is an alkali metal, alkaline earth metal, element of Group 13 to Group 16, transition metal, rare earth element, or a combination thereof, and is not Si), Sn, SnO2, and Sn-Y alloy (Y is an alkali metal, alkaline earth metal, element of Group 13 to Group 16, transition metal, rare earth element, or a combination thereof, and is not Sn), or include a mixture of at least one selected therefrom and SiO2. Examples of Y include Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0053] In the negative electrode active material slurry, the conductive material (conducting material), binder, and solvent can be the same as or substantially the same as those used in preparing the positive electrode. For example, the conductive material can be the same as or substantially the same as the additive described with reference to the positive electrode material. In some embodiments, a plasticizer can be independently added to each of the positive electrode active material slurry and the negative electrode active material slurry to form pores in the electrode plate.

[0054] The amounts of the negative electrode active material, conductive material (conducting material), binder, and solvent can be the same as or substantially the same as those commonly used in lithium batteries. If desired according to the use and structure of the lithium battery, at least one of the conductive material (conducting material), binder, and solvent can be omitted.

[0055] Next, in some embodiments, a separator to be disposed between the positive electrode and the negative electrode is prepared. The separator can be any suitable separator available in the art commonly used in lithium batteries. A separator with low resistance to the movement of electrolyte ions and high electrolyte absorption can be used. For example, in some embodiments, the separator is selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE) and combinations thereof, each of which can be provided in the form of a non-woven fabric or a fabric. For example, a windable separator such as polyethylene or polypropylene can be used in a lithium ion battery, and a separator with high organic electrolyte absorption can be used in a lithium ion polymer battery. For example, according to some embodiments, a separator can be prepared as follows.

[0056] The separator component is prepared by mixing a polymer resin, a filler and a solvent. The separator component can be coated (directly coated) and dried on the electrode to complete the formation of the separator. In some embodiments, the separator component can be cast on a separate support and then the film separated from the support is stacked on the electrode, thereby completing the formation of the separator.

[0057] The polymer resin used in preparing the separator is not particularly limited, and any suitable material used as a binder for electrode plates can be used. For example, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a mixture thereof can be used.

[0058] Then, in some embodiments, an electrolyte is prepared.

[0059] For example, the electrolyte may be solid. For example, boron oxide, lithium oxynitride, etc. may be used, but the electrolyte is not limited thereto, and the electrolyte may be any one of various suitable materials that are generally used as solid electrolytes in the art. The solid electrolyte may be formed on the negative electrode by, for example, sputtering.

[0060] For example, an organic electrolyte solution may be prepared by dissolving a lithium salt in an organic solvent.

[0061] The organic solvent can be any one of various suitable materials that can be used as an organic solvent in the art. For example, the organic solvent can be propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-ethylene glycol dimethyl ether, cyclopentane, ethylene dichloride, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether or a mixture thereof.

[0062] The lithium salt may be any one of various suitable lithium salts used in the art. For example, the lithium salt may be LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein, x and y are natural numbers), LiCl, LiI or a mixture thereof.

[0063] Figure 5 is an exploded perspective view of the lithium battery 100 .

[0064] The lithium battery 100 includes a positive electrode 114, a separator 113 and a negative electrode 112. The positive electrode 114, the separator 113 and the negative electrode 112 are wound or folded to be placed in a battery housing 120. Then, an organic electrolyte solution is injected into the battery housing 120, and the battery housing 120 is sealed with a cap assembly 140 to complete the manufacture of the lithium battery 100. The battery housing 120 can be cylindrical (cylindrical type), rectangular (rectangular type) or thin film (thin film type). For example, the lithium battery 100 can be a large thin film type battery (large thin film type battery). The lithium battery 100 can be a lithium ion battery or can include a battery assembly. The battery assembly can be stacked in a dual battery structure, the resulting structure can be immersed in an organic electrolyte solution, and the result obtained is placed in a bag, which is then sealed to complete the manufacture of a lithium ion polymer battery.

[0065] The range may be, for example, about 2 mA / cm 2 Up to about 8mA / cm 2 The lithium battery 100 is used at a current density of about 2 mA / cm 2 Up to about 8mA / cm 2 The lithium battery 100 may be used in an electric vehicle (EV) or a plug-in hybrid electric vehicle (PHEV) (eg, the lithium battery is configured to power an EV or a PHEV).

[0066] Additionally, in some embodiments, multiple battery assemblies may be stacked and formed into a battery pack. Figure 6 2 is a perspective view schematically showing the battery pack 10. Figure 6 As shown in FIG. 1 , the battery pack 10 includes a plurality of battery assemblies 400 , a cooling member 200 , and a housing 300 . The plurality of battery assemblies 400 are arranged in a row, side by side. The battery cells 100 may be accommodated in the housing 300 .

[0067] Hereinafter, one or more embodiments will be described with reference to the following examples. However, these examples are not intended to limit the scope of one or more embodiments.

[0068] Additionally, details related to one or more embodiments that should be readily understood by one of ordinary skill in the art are not repeated herein.

[0069] [Example]

[0070] (Preparation of positive electrode)

[0071] Example 1: Preparation of positive electrode

[0072] 92wt% of the positive electrode active material (LiNi 0.33 Co 0.33 Mn 0.33 O2), 3wt% secondary particles of carbon material (each having about 20 primary particles bonded (or connected) to each other, wherein the average particle size of the primary particles is about 23nm), 1wt% flake graphite (Timcal can be used) and 4wt% polyvinylidene fluoride (PVdF, 6020) was dispersed in N-methylpyrrolidone (NMP) to prepare a positive electrode active material slurry, and the wt% was based on the total weight of the positive electrode active material slurry. Here, the specific surface area of ​​the carbon material is about 150 m 2 / g, and the oil absorption (OAN) of the carbon material is about 160 ml / 100 g.

[0073] The positive electrode active material slurry was coated on an aluminum (Al) foil having a thickness of about 12 μm by bar coating. Here, the thickness of the Al foil on which the positive electrode active material slurry was coated was about 183 μm.

[0074] The obtained Al foil coated with the positive electrode active material slurry was placed in a furnace, preliminarily dried at 90°C for about 2 hours to evaporate NMP, and placed in a vacuum furnace, and secondary dried at 120°C for about 2 hours to complete or substantially complete the evaporation of NMP. The product was rolled and punched to prepare a positive electrode with a thickness of about 140 μm. Here, the capacity of the positive electrode is about 2.47 mAh / cm 2 To about 2.88 mAh / cm 2 In the range of , the mixed density of the positive electrode is about 3.193 g / cc, and the amount of the solid of the positive electrode material is about 68.63 wt % based on the total weight of the positive electrode.

[0075] Example 2: Preparation of positive electrode

[0076] 92 wt% of the positive electrode active material (by mixing LiNi 0.33 Co0.33 Mn 0.33 O2 and LiMnO2), 4 wt% of secondary particles of carbon material (each having about 20 primary particles bonded (or connected) to each other, wherein the average particle size of the primary particles is about 23 nm), and 4 wt% of polyvinylidene fluoride (PVdF, 6020) is dispersed in NMP to prepare a positive electrode active material slurry, and the wt% is based on the total weight of the positive electrode active material slurry. Here, the specific surface area of ​​the carbon material is about 150 m 2 / g, and the oil absorption of the carbon material is about 160ml / 100g.

[0077] The positive electrode active material slurry was coated on an Al foil having a thickness of about 12 μm by bar coating. Here, the thickness of the Al foil on which the positive electrode active material slurry was coated was about 180 μm.

[0078] The obtained Al foil coated with the positive active material slurry was placed in a furnace, preliminarily dried at 90°C for about 2 hours to evaporate NMP, and placed in a vacuum furnace, and secondary dried at 120°C for about 2 hours to complete or substantially complete the evaporation of NMP. The product was rolled and punched to prepare a positive electrode with a thickness of about 133 μm. Here, the capacity of the positive electrode is about 175 mAh / cm 2 , the positive electrode loading level is about 32.74 mg / cm 2 .

[0079] Comparative Example 1: Preparation of positive electrode

[0080] 92wt% of the positive electrode active material (LiNi 0.33 Co 0.33 Mn 0.33 O2), 3wt% secondary particles of carbon material (each having about 50 primary particles bonded (or connected) to each other, wherein the average particle size of the primary particles is about 31nm), 1wt% flake graphite (Timcal can be used) and 4wt% polyvinylidene fluoride (PVdF, 6020) is dispersed in NMP to prepare a positive electrode active material slurry, and the wt% is based on the total weight of the positive electrode active material slurry. Here, the specific surface area of ​​the carbon material is about 50m 2 / g to about 70m 2 / g, and the oil absorption of the carbon material is in the range of about 220 ml / 100 g to about 300 ml / 100 g.

[0081] The positive electrode active material slurry was coated on an Al foil having a thickness of about 12 μm by bar coating. Here, the thickness of the Al foil on which the positive electrode active material slurry was coated was about 170 μm.

[0082] The obtained Al foil coated with the positive electrode active material slurry was placed in a furnace, preliminarily dried at 90°C for about 2 hours to evaporate NMP, and placed in a vacuum furnace, and secondary dried at 120°C for about 2 hours to complete or substantially complete the evaporation of NMP. The product was rolled and punched to prepare a positive electrode with a thickness of about 128 μm. Here, the capacity of the positive electrode is about 2.47 mAh / cm 2 To about 2.88 mAh / cm 2 In the range of , the mixed density of the positive electrode is about 3.2 g / cc, and the amount of the solid of the positive electrode material is about 63.73 wt % based on the total weight of the positive electrode.

[0083] Comparative Example 2: Preparation of positive electrode

[0084] 92 wt% of the positive electrode active material (by mixing LiNi 0.33 Co 0.33 Mn 0.33 O2 and LiMnO2), 4 wt% of secondary particles of carbon material (each having about 50 primary particles bonded (or connected) to each other, wherein the average particle size of the primary particles is about 31 nm), and 4 wt% of polyvinylidene fluoride (PVdF, 6020) is dispersed in NMP to prepare a positive electrode active material slurry, and the wt% is based on the total weight of the positive electrode active material slurry. Here, the specific surface area of ​​the carbon material is about 50m 2 / g to about 70m 2 / g, and the oil absorption of the carbon material is in the range of about 220 ml / 100 g to about 300 ml / 100 g.

[0085] The positive electrode active material slurry was coated on an Al foil having a thickness of about 12 μm by bar coating. Here, the thickness of the Al foil on which the positive electrode active material slurry was coated was about 189 μm.

[0086] The obtained Al foil coated with the positive active material slurry was placed in a furnace, preliminarily dried at 90°C for about 2 hours to evaporate NMP, and placed in a vacuum furnace, and secondary dried at 120°C for about 2 hours to complete or substantially complete the evaporation of NMP. The product was rolled and punched to prepare a positive electrode with a thickness of about 133 μm. Here, the capacity of the positive electrode is about 175 mAh / cm 2 , the positive electrode loading level is about 32.74 mg / cm 2 .

[0087] (Manufacturing lithium batteries)

[0088] Example 3: Manufacturing lithium batteries

[0089] (Preparation of negative electrode)

[0090] 97.5 wt % of graphite (available from Mitsubishi Chemical) and 2.5 wt % of carboxymethyl cellulose (CMC) / styrene butadiene rubber (SBR) solution were added to an agate mortar and mixed to prepare a negative electrode active material slurry. The negative electrode active material slurry was coated on a copper foil having a thickness of about 8 μm by rod coating. The obtained copper foil having the negative electrode active material slurry coated thereon was placed in a furnace, dried at 25° C. for about 10 hours, and then rolled and punched to prepare a negative electrode having a thickness of 133 μm.

[0091] (Preparation of Electrolyte)

[0092] The electrolyte was prepared by dissolving 1.15 M LiPF6 lithium salt in a mixed solvent including ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate (in a volume ratio of EC / DEC / EMC=1:1:1).

[0093] (Manufacturing lithium batteries)

[0094] A 90 Ah battery was prepared using the positive electrode, negative electrode, electrolyte, and polyethylene separator (Celgard 2320) prepared according to Example 1.

[0095] Example 4: Manufacturing lithium batteries

[0096] (Preparation of negative electrode)

[0097] 97.5 wt % of graphite (available from Mitsubishi Chemical) and 2.5 wt % of carboxymethyl cellulose (CMC) / styrene butadiene rubber (SBR) solution were added to an agate mortar and mixed to prepare a negative electrode active material slurry. The negative electrode active material slurry was coated on a copper foil having a thickness of 8 μm by rod coating. The obtained copper foil having the negative electrode active material slurry coated thereon was placed in a furnace, dried at 25° C. for about 10 hours, and then rolled and punched to prepare a negative electrode having a thickness of 102 μm.

[0098] (Preparation of Electrolyte)

[0099] The electrolyte was prepared by dissolving 1.15 M LiPF6 lithium salt in a mixed solvent including ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate (in a volume ratio of EC / DEC / EMC=1:1:1).

[0100] (Manufacturing lithium batteries)

[0101] A 18650 battery was prepared using the positive electrode prepared according to Example 2, the negative electrode, the electrolyte, and a polyethylene separator (Celgard 2320).

[0102] Comparative Example 3: Manufacturing Lithium Batteries

[0103] A 90 Ah battery was manufactured in the same method as described in Reference Example 3, except that the negative electrode prepared according to Comparative Example 1 was used instead of the negative electrode prepared according to Example 1.

[0104] Comparative Example 4: Manufacturing Lithium Batteries

[0105] A 18650 battery was manufactured in the same method as described in Reference Example 4, except that the negative electrode prepared according to Comparative Example 2 was used instead of the negative electrode prepared according to Example 2.

[0106] Analysis Example 1: Transmission Electron Microscope (TEM) Image and Scanning Electron Microscope (SEM) Image

[0107] The positive electrode material on the surface of each positive electrode prepared according to Example 1 and Comparative Example 1 was observed using a transmission electron microscope (HR-TEM) at a resolution ranging from tens of nanometers (nm) to several nm. The results are shown in FIG. 2A to FIG. 2D middle.

[0108] Reference Figures 2A to 2D , it was confirmed that the average particle size of the primary particles of the positive electrode material on the surface of the positive electrode prepared according to Example 1 was 23 nm, and the average particle size of the primary particles of the positive electrode material on the surface of the positive electrode prepared according to Comparative Example 1 was 31 nm. Therefore, it was confirmed that the positive electrode material on the surface of the positive electrode prepared according to Example 1 had an average chain length of 20 primary particles that were equal to or less than that combined (or connected) with each other, while the positive electrode material on the surface of the positive electrode prepared according to Comparative Example 1 had an average chain length of more than 50 primary particles that were combined (or connected) with each other.

[0109] In addition, the positive electrode material on the surface of each positive electrode prepared according to Example 1 and Comparative Example 1 was observed at a resolution of several hundred nm by using a scanning electron microscope (SEM, purchased from Hitachi, model: S-5500). The results are shown in Figure 3A and Figure 3B middle.

[0110] Reference Figure 3A and Figure 3B , compared with the positive electrode material on the surface of the positive electrode prepared according to Comparative Example 1, the positive electrode material on the surface of the positive electrode prepared according to Example 1 is substantially uniformly and homogeneously distributed on the positive electrode active material core.

[0111] Analysis Example 2: Viscosity Variation Properties

[0112] The viscosity variation properties of the positive electrode materials on the surface of each positive electrode prepared according to Example 1 and Comparative Example 1 according to the shear rate were analyzed. The results are shown in Figure 4 and Table 1.

[0113] Table 1

[0114]

[0115] Reference Figure 4 and Table 1, it can be confirmed that the viscosity change according to the shear rate of the positive electrode material on the surface of the positive electrode prepared according to Example 1 shows highly stable movement, compared with the viscosity change according to the shear rate of the positive electrode material on the surface of the positive electrode prepared according to Comparative Example 1. In this regard, it is determined that the carbon material on the positive electrode active material core included in the positive electrode material on the surface of the positive electrode prepared according to Example 1 can be dispersed in a relatively short period of time, compared with the carbon material on the positive electrode active material core included in the positive electrode material on the surface of the positive electrode prepared according to Comparative Example 1, and therefore, the positive electrode material prepared according to Example 1 can have a stable viscosity.

[0116] Evaluation Example 1: Evaluation of curvature

[0117] The curvature of each positive electrode prepared according to Example 1 and Comparative Example 1 was evaluated. The results are shown in Table 2. The curvature was evaluated in terms of length by cutting each electrode plate of the positive electrode into a size of 145 mm×4 m, bending the electrode plate to form a bend to the maximum extent, and measuring the longest bending distance from a horizontal line to the electrode plate, wherein the horizontal line is a straight line formed by combining (or connecting) both ends of the electrode plate (e.g., to each other).

[0118] Table 2

[0119] Curvature(mm) Example 1 2.5 Comparative Example 1 8.0

[0120] Referring to Table 2, it can be confirmed that the curvature of the positive electrode prepared according to Example 1 is about 1 / 3 or less of the curvature of the positive electrode prepared according to Comparative Example 1. In this regard, it is determined that the positive electrode prepared according to Example 1 has a higher energy density than that of the positive electrode prepared according to Comparative Example 1.

[0121] Evaluation Example 2: Evaluation of Adhesive Strength

[0122] The bonding strength between the positive electrode material and the current collector of each positive electrode prepared according to Example 2 and Comparative Example 2 was evaluated. The results are shown in Table 3. The electrode plate of the positive electrode was cut into a size of 20 mm × 100 mm, and the force (gf / mm) of separating the positive electrode material prepared according to Example 2 and Comparative Example 2 from the current collector was measured by performing a 180 degree peel test using a tensile strength tester from Instron, and each bonding strength was evaluated. The results are shown in Table 3.

[0123] Table 3

[0124] Bond strength (gf / mm) Example 2 2.0 Comparative Example 2 1.1

[0125] Referring to Table 3, the bonding strength between the positive electrode material and the current collector of the positive electrode prepared according to Example 2 was about 1.5 gf / mm or more, which was higher than that of the positive electrode material and the current collector of the positive electrode prepared according to Comparative Example 2.

[0126] Evaluation Example 3: Evaluation of Internal Resistance

[0127] The internal resistance of each lithium battery prepared according to Example 3 and Comparative Example 3 was measured at 25°C. The results are shown in Figure 7 and Table 4. Five lithium batteries were manufactured according to Example 3 and five lithium batteries were manufactured according to Comparative Example 3, and the lithium batteries were charged / discharged at a current of 1 / 3C for 10 seconds at SOC20%, SOC50%, and SOC90%, and the internal resistance was measured. Here, SOC20%, SOC50%, and SOC90% respectively represent the state of charge of 20% charge capacity, 50% charge capacity, and 90% charge capacity of the battery when the total charge capacity of the battery is 100%. The results are shown in Figure 7 and Table 4.

[0128] Table 4

[0129]

[0130] Reference Figure 7 From Table 4, it can be confirmed that the internal resistance at SOC 20%, SOC 50% and SOC 90% during the discharge process of the lithium battery of Example 3 is reduced by about 3% to about 4% compared with the internal resistance during the discharge process of the lithium battery of Comparative Example 3.

[0131] Evaluation Example 4: Evaluation of life characteristics

[0132] 4.1: Evaluation of charge / discharge characteristics

[0133] The charge / discharge characteristics of each lithium battery prepared according to Example 3 and Comparative Example 3 were evaluated. Each lithium battery prepared according to Example 3 and Comparative Example 3 was subjected to two formation charge / discharges (e.g., two formation charge / discharges), charged at a rate of 0.2C until the voltage of the lithium battery reached 4.12V, and then discharged at a rate of 0.2C until the voltage of the lithium battery reached 2.7V. Here, the charge / discharge conditions are standard charge / discharge conditions, and the discharge capacity used here is a standard capacity.

[0134] Next, the lithium battery is charged at a rate of 1C and discharged at a rate of 1C in a method that is the same as or substantially the same as described above until the voltage of the lithium battery reaches 2.7V. Here, the discharge capacity (discharge capacity after the 1st cycle) is measured. The charge / discharge process is repeated to evaluate the life characteristics of the lithium battery. The discharge capacity after each cycle and the discharge capacity after the 400th cycle of each lithium battery are measured, and the capacity retention rate is calculated therefrom. The capacity retention rate (%) is defined as in Equation 1. The results are shown in Table 5.

[0135] Equation 1

[0136] Capacity retention rate (%) = discharge capacity after 400th cycle / discharge capacity after 1st cycle

[0137] Table 5

[0138]

[0139] Referring to Table 5, it can be confirmed that the discharge capacity and capacity retention rate of the lithium battery prepared according to Example 3 are better than those of the lithium battery prepared according to Comparative Example 3.

[0140] 4.2: Evaluation of high temperature storage characteristics

[0141] According to the same or substantially the same method as described in reference 4.1, the high temperature storage characteristics of each lithium battery prepared according to Example 3 and Comparative Example 3 after 2 cycles of formation charge / discharge were evaluated. In order to evaluate the high temperature storage characteristics, each lithium battery prepared according to Example 3 and Comparative Example 3 was charged at a rate of 1C in a room at room temperature until the voltage of the lithium battery reached 4.12V, and then discharged at a rate of 1C until the voltage of the lithium battery reached 2.7V. Here, the discharge capacity (discharge capacity after the 1st cycle) was measured. The lithium battery was placed in a room at a temperature of 60°C for 60 days. Then, the discharge capacity (discharge capacity after 60 days) was measured, and the capacity retention rate was calculated therefrom. Here, the capacity retention rate (%) is defined as the % value obtained by dividing the discharge capacity after 60 days by the discharge capacity after the 1st cycle. The results are shown in Figure 8 and Table 6.

[0142] Table 6

[0143]

[0144] Reference Figure 8 From Table 6, it can be confirmed that the capacity retention rate of the lithium battery prepared according to Example 3 is better than the capacity retention rate of the lithium battery prepared according to Comparative Example 3.

[0145] 4.3: Evaluation of life characteristics by using reference performance tests

[0146] The life characteristics of each lithium battery prepared according to Example 4 and Comparative Example 4 after two formation charge / discharges were evaluated using a reference performance test in the same or substantially the same method as described in reference 4.1. In order to evaluate the life characteristics, each lithium battery prepared according to Example 4 and Comparative Example 4 was charged at a rate of 0.5C until the voltage of the lithium battery reached 4.12V, and then discharged at a rate of 0.2C until the voltage of the lithium battery reached 2.7V. Here, the charge / discharge conditions are standard charge / discharge conditions, and the discharge capacity used here is a standard capacity.

[0147] Next, the lithium battery was charged at a rate of 2C and discharged at a rate of 3C in a method that was the same or substantially the same as described above until the voltage of the lithium battery reached 2.7V. Here, the discharge capacity (discharge capacity after the 1st cycle) was measured. The charge / discharge process was repeated to evaluate the life characteristics of the lithium battery. The discharge capacity after each cycle and the discharge capacity after the 400th cycle were measured for each lithium battery, and the capacity retention rate was calculated therefrom. The capacity retention rate (%) is defined as in Equation 1. The results are shown in Fig. 9 and Table 7.

[0148] Table 7

[0149]

[0150] Reference Fig. 9 From Table 7, it can be confirmed that the discharge capacity and capacity retention rate of the lithium battery prepared according to Example 4 are better than those of the lithium battery prepared according to Comparative Example 4.

[0151] As described above, the positive electrode material according to the above embodiment can increase the battery capacity and reduce the resistance, so it is possible to provide a positive electrode and a lithium battery with high energy density and / or long life characteristics. In addition, the positive electrode material can reduce the amount of the organic solvent used in the preparation, so the manufacturing cost of the positive electrode material can be reduced. Therefore, it is possible to prepare a positive electrode material with high energy density and / or long life characteristics (for example, by increasing the battery capacity and reducing the resistance), a positive electrode including a positive electrode material, and a lithium battery including a positive electrode.

[0152] It should be understood that the exemplary embodiments described herein should be considered in a descriptive sense only and not for purposes of limitation. Descriptions of features or aspects in each exemplary embodiment should typically be considered as available for other similar features or aspects in other exemplary embodiments.

[0153] Although one or more example embodiments have been described with reference to the drawings, it will be understood by those skilled in the art that various changes in form and details may be made without departing from the spirit and scope defined by the claims and their equivalents.

Claims

1. A positive electrode material comprising: Positive electrode active material; as well as The conductive material is composed of a secondary particle carbon material, and the secondary particle carbon material is composed of a plurality of primary particles, wherein the carbon material of the secondary particles has an average chain length of less than 20 primary particles bonded to each other, and wherein the average particle size of the primary particles is 23 nm, and wherein the amount of the carbon material is in the range of 3 wt % to 4 wt % based on the total weight of the positive electrode material, Among them, the specific surface area of ​​carbon material is 150m 2 / g, The oil absorption of the carbon material is 160 ml / 100 g, and the oil absorption of the carbon material is obtained by using the ASTM D2414 test method.

2. The positive electrode material according to claim 1, wherein The carbon material includes at least one selected from carbon black and aerogel.

3. The positive electrode material according to claim 1, wherein The positive electrode material further includes at least one additive selected from natural graphite, artificial graphite, carbon black, carbon fiber, metal powder and metal fiber.

4. The positive electrode material according to claim 3, wherein The amount of the additive is in the range of 0.1 wt % to 15 wt % based on the total weight of the positive electrode material.

5. The positive electrode material according to claim 1, wherein The positive electrode material also includes a binder.

6. The positive electrode material according to claim 5, wherein The amount of the binder is in the range of 0.1 wt % to 15 wt % based on the total weight of the positive electrode material.

7. The positive electrode material according to claim 1, wherein The positive electrode active material includes at least one selected from the following substances: lithium nickel oxide; lithium cobalt oxide; lithium cobalt aluminum oxide; lithium nickel cobalt manganese oxide; lithium manganese oxide; lithium nickel oxide doped with at least one selected from chromium, zirconium and titanium; lithium cobalt oxide doped with at least one selected from chromium, zirconium and titanium; lithium cobalt aluminum oxide doped with at least one selected from chromium, zirconium and titanium; lithium nickel cobalt manganese oxide doped with at least one selected from chromium, zirconium and titanium; lithium manganese oxide doped with at least one selected from chromium, zirconium and titanium; olivine-based oxide.

8. A positive electrode, comprising: The positive electrode material according to claim 1; as well as Current collector.

9. The positive electrode according to claim 8, wherein The amount of solid of the positive electrode material is 65 wt % or more based on the total weight of the positive electrode.

10. The positive electrode according to claim 9, wherein The bonding strength between the positive electrode material and the current collector is 1.5 gf / mm or more.

11. The positive electrode according to claim 8, wherein The specific resistance of the positive electrode is 12 milliohms or less.

12. A lithium battery comprising: A positive electrode, comprising the positive electrode material according to claim 1; A negative electrode, including a negative electrode active material; as well as The electrolyte is located between the positive and negative electrodes.

13. The lithium battery according to claim 12, wherein: The negative electrode active material includes at least one selected from a material capable of reversibly inserting and extracting lithium ions, lithium metal, and a metal material capable of forming an alloy with lithium.

14. The lithium battery according to claim 12, wherein: Lithium batteries are constructed to operate in the range of 2 mA / cm 2 Up to 8mA / cm 2 Operate at a current density of .

15. The lithium battery according to claim 12, wherein: Lithium batteries are configured to power electric vehicles or plug-in electric vehicles.

Citation Information

Patent Citations

  • Positive electrode material for lithium-ion secondary battery and lithium-ion secondary battery

    WO2013042591A1

  • Nonaqueous electrolyte secondary battery

    WO2014038001A1